Analysis of Maslahah Mursalah on the Choice of Tabattul Lifestyle - M. Yusuf Alfi Sahrin; Iwan Iwan (Hikmah, 2025)
The phenomenon of tabattul, or living a bachelor life without the desire to marry, is increasingly found in Sei Bamban Village, Batang Serangan District, Langkat Regency. Based on observations, there are about twenty people over the age of forty who choose not to marry due to economic factors and concerns about not being able to provide for a spouse. This study aims to analyze this phenomenon from the perspective of maslahah mursalah. The approach used is descriptive qualitative through observation, interviews, and documentation techniques. The results of the study show that the practice of tabattul is not in line with the principles of Islamic teachings and does not meet the criteria of maslahah. According to the Indonesian Ulema Council of Batang Serangan Subdistrict, Islam encourages marriage as the sunnah of the Prophet Muhammad and a means of preserving lineage, honor, and social stability. This study concludes that the decision to remain single without a shar'i reason has the potential to cause social mafsadah, such as alienation and the weakening of family values. The implications of this study emphasize the need for contextual da'wah strategies and economic empowerment programs so that the community can re-understand the meaning of the maslahah of marriage in Islamic life.